Geração de subsídios para a tomada de decisão na cadeia produtiva da bovinocultura do Brasil - Vicini, Lorena (2006)
The search for products that would reach a certain level of quality has been significantly growing lately, thus forcing producers to insert their product in certain quality levels elected by the consumer market, under the risk of being excluded of it. Nowadays, due to those demands, quality, low prices, costs reduction are wanted. It all makes necessary to start the process for changes that would improve farming conditions. The advance of technology also wants the farmer to adapt to the new scenery, to do so it is needed a study of the livestock situation in Brazil from 1997 to 2004, which is the objective of this work. Initially, a descriptive statistics was applied, which allowed to verify the behaviour of the variables analyzed. Secondly, the techniques of the multivaried analyses were used, that is, group analysis that allow to identify similar variables according to each group. Later, a factors analysis was applied, and reduced the dimension of the problem by using some factors only to better explain the original variables. Then, after determining the number of factors to be used, was applied the principal components analysis method, which allowed to identifying in what States the livestock is not expressive. Thirdly, it was applied the temporal series method only to those States with expression in bovine production. It was also monitoring the live cattle prices in the period analyzed 1997 the 2004 which affects directly the production. From that data, it was possible to make the prevision for 2005 and 2006, in order to support farmers to draw their objectives. The results will work as support to create taxes incentive policies for the development of this economic sector. Therefore, this research is relevant as in the whole country will be possible to draw aims to be reached based on the future development of subsidies.